Analysis of genetic sequence variation in Formicidae NCBI popset 1871743971 using in silico RFLP - Muhamad Zacky Pryatna; Rijal Satria; Afifatul Achyar (Genetikawan Muda Indonesia, 2024)
In practically every region of the world, with the exception of the poles, ants are a common form of insect. This one organism lives in colonies and cooperates, therefore these insects are referred to as social insects. In an ant colony, three types of castes have their respective roles and functions, namely, there are queen ants, worker ants, and male ants. In one ant species, many colonies live scattered and each of them has different genes that are influenced by environmental factors and other factors. The purpose of this study was to determine and analyze the genetic variation of ants with the WNT-1 gene sequence in NCBI popset 1871743971. This research was conducted in May-June 2023 using the RFLP method in silico. Based on the results of the study, it was found that there were genetic variations in the WNT-1 gene sequence in Formicidae available at NCBI in PopSet 1871743971.